Opportunistic secure transmission scheme for simultaneous wireless information and power transfer - Keming MA; Yajun CHEN; Xin HU; Kaizhi HUANG; Xinsheng JI (Tongxin xuebao)
Aiming at the different requirements of energy transmission and information transmission in simultaneous wireless information and power transfer (SWIPT),an opportunistic transmission scheme was proposed for enhancing physical layer security.Firstly,a SWIPT network with multi-cells was considered where multi-users,multi-eavesdroppers and the users were assumed to adopt time-switching based receivers and employ non-linear conversion model to harvest energy.The transmitter could dynamically switch between information transmission and power transfer according to the channel state,breaking the traditional fixed slot allocation scheme of energy transmission and information transmission.On this basis,the performances of energy transmission and information transmission were analyzed comprehensively,including the stability and efficiency of energy transmission,and the reliability and security of information transmission in the scenario of independent eavesdropping and joint eavesdropping.Next,a switching threshold optimization model was given to maximize its secrecy throughput under the constraint of the energy transmission,the reliability and secrecy performance requirements of information transmission.Finally,simulation results verify the validity of the proposed scheme.